MODAL KULTURAL KAKANTARAN TOMBULU : SAKO MELENG ULALAN LAMPANGAN - Pua, Christo; Palit, Anatje; Terok, Rafael (Kajian Linguistik, 2020)
The contents of the traditional cultural include social resources and cultural capital. This writing is only limited to cultural capital. Cultural capital is a traditional capital, cultural value and norm also local wisdom used to empowered human life in order to make a peaceful and prosperous society. The paradigm of this research is in the form of qualitative research because in this study the form and meaning of the text of a song was explored, found, disclosed, and explained. The form is related to the structure of the text morphologically, whereas the meaning is related to the content that is understood as a value, norm, or local wisdom. Thus, the purpose of this paper is to describe 1) the morphological form of Kakantara Tombulu sa ko meleng ulalan lampangan, and 2) the contents or meanings related to values, norms, local wisdom in the song. Data collection is done by observation and interviews. The observers are the perpetrators of this oral tradition especially when they sing this song together (the atmosphere of joy displayed), and the listeners or connoisseurs of this tradition (passive audience). Interviews were carried out to informants who played an active role or as perpetrators of oral traditions. These observations and interviews were carried out in the city of Tomohon, precisely in the Kakaskasen area, which according to the writer’s observation they sing the songs in Tombulu language actively. The result of the study shows that the song of Sa ko meleng lampangan was the thanksgiving song of the ethnic Tombulu who had 1) the structure of the language morphologically morphophemis and has polymorphic morpheme. Thus, this morphological process (affixation and reduplication) forms a new meaning or reinforces the meaning as mentioned by the basic word; 2) Cultural capital can be seen in the form of cultural values and norms which are reflected through the values of faith, brotherhood, friendship, and sincerity implemented by the practitioners or connoisseurs of oral tradition which is bound by certain norms and has become the source of peace and prosperity as the core of local wisdom of the people of Tombulu.Keywords: cultural capital: values, norms, local wisdom